2013
DOI: 10.1371/journal.pone.0083885
|View full text |Cite
|
Sign up to set email alerts
|

Training and Transfer of Training in Rapid Visual Search for Camouflaged Targets

Abstract: Previous examinations of search under camouflage conditions have reported that performance improves with training and that training can engender near perfect transfer to similar, but novel camouflage-type displays [1]. What remains unclear, however, are the cognitive mechanisms underlying these training improvements and transfer benefits. On the one hand, improvements and transfer benefits might be associated with higher-level overt strategy shifts, such as through the restriction of eye movements to target-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Analysis of eye movement data suggested that these reaction time improvements were subserved by improvements in both search guidance and decision making mechanisms (improvements in both Search and Verification Times). The latter finding is consistent with a number of previous studies [ 2 , 22 ] and may suggest that with increased task familiarity comes an improvement in segmentation processes. With practice, observers are better able to extract target-related information from the background region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of eye movement data suggested that these reaction time improvements were subserved by improvements in both search guidance and decision making mechanisms (improvements in both Search and Verification Times). The latter finding is consistent with a number of previous studies [ 2 , 22 ] and may suggest that with increased task familiarity comes an improvement in segmentation processes. With practice, observers are better able to extract target-related information from the background region.…”
Section: Discussionsupporting
confidence: 93%
“…Size of the search target was also manipulated, with smaller targets resulting in a more difficult search task. Consistent with previous studies by Neider and colleagues [ 2 , 6 , 8 ], we predicted that accuracy and reaction times (RT) would worsen with increasing target difficulty, but that participants might show improvements in those measures as familiarity of the tasks increased (based on training improvements reported in [ 6 , 8 , 22 ]). Additionally, consistent with previous studies of search for well-defined targets compared to categorically defined targets [ 11 , 13 ], we predicted that overall performance would be better in Experiment 1 when participants were provided with a perfect visual template for each search trial compared to Experiment 2, when participants could not search from a perfect template.…”
Section: Introductionsupporting
confidence: 83%
“…However, this was not done on an RSVP task with real-world stimuli, but rather on a series of simple stimuli (a number of circles arranged within a larger circle) that were sequentially and randomly flashed for 2 seconds each. While this technique could, in principle, be extended to the real-world stimuli used in this paper, it is unlikely that it could work when images are presented at the high speeds used in RSVP, as there are previous reports of saccades being suppressed at such rates [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%